Consumption of foods and beverages in elementary schools: Results of the implementation of the general guidelines for foods and beverages sales in elementary schools in Mexico, stages II and III. (February 2018) - López-Olmedo, Nancy; Jiménez-Aguilar, Alejandra; Morales-Ruan, María del Carmen; Hernández-Ávila, Mauricio; Shamah-Levy, Teresa; Rivera-Dommarco, Juan A.
Highlights: The main findings showing that: Children who consume food brought from home and purchased at school take in the highest amounts of energy. There is a need to step up the promotion of healthier eating models and food preparation at home. Guidelines are a key action for the contention of overweight in elementary schools. It is mandatory regularly monitor compliance with the Guidelines in Mexico. We need support networks between countries that guarantee children's health. Abstract: The Mexican government developed the General Guidelines for the dispensing or distribution of foods and beverages at food sales in elementary schools (Guidelines). The objective is to evaluate the consumption of food and beverages during school hours, in two different stages of the implementation of the Guidelines: stages II (2011–2012) and stage III (2012–2013) in 565 elementary school students. We constructed three categories of consumption according to the origin of food: Home, food brought from home; School, food purchased at school and Both, food from home and food purchased at school. The main results showed that there are differences in both stages in energy intake according to the foods' origin; the category of School has the lowest energy and macronutrients consumption, as well as the closer compliance with de Guidelines recommendations in both stages, while the category of Both has a higher consumption and the less compliance with the Guidelines. This may be indicating an improvement in school guidelines and it is also reflecting the need to reinforce orientation for a healthy diet with respect to foods brought from home. It is necessary to continue with periodic evaluations to measure fulfillment with the Guidelines.